Anterior uveitis, an extrahepatic manifestation of hepatitis B virus infection: A case report - Narayan Kurmi, Ram; Kumar Ranjan, Mukesh; Baniya, Abinash (Journal of Chitwan Medical College, 2024)
Anterior uveitis is one of the most common forms of uveitis encountered in outpatient department. The etiology of uveitis ranges from infectious to noninfectious causes (e.g. virus, bacteria, autoimmune, idiopathic). We present a case of acute anterior granulomatous uveitis in 65 years old male patient who presented with a complaint of pain, redness and blurry vision for 5 days in his right eye. All the routine investigations were done to find the aetiology of the disease which showed positive HBsAg, RA factor and Mantoux test. However, rheumatoid arthritis and tuberculosis were ruled out as test result may be false positive because of various causes. Although the Hepatitis B virus is the hepatotropic, it leads to many extrahepatic manifestations such as glomerulonephritis, polyarteritis nodosa, polymyalgia rheumatica, essential mixed cryoglobulinemia and arthralgia which was reported in previous studies. The mechanism of extrahepatic manifestation of hepatitis B virus infection was unknown, however, the immune complex deposition is the most likely etiological cause. We report a rare case of Hepatitis B virus manifesting as acute anterior granulomatous uveitis.